Serum and dietary magnesium and incidence of atrial fibrillation in whites and in African Americans: Atherosclerosis risk in communities (ARIC) study - Misialek, J.; Lopez, F.; Lutsey, P.; Huxley, Rachel; Peacock, J.; Chen, L.; Soliman, E.; Agarwal, S.; Alonso, A. (2013)
Background: Low serum magnesium (Mg) has been associated with an increased risk of cardiovascular disease (CVD), including ventricular arrhythmias, but the association between serum or dietary Mg and atrial fibrillation (AF) has not been investigated. Methods and Results: A total of 14,290 men and women (75% white; 53% female; mean age, 54 years) free of AF at baseline participating in the Atherosclerosis Risk in Communities study in the United States, were studied. Incident AF cases through 2009 were ascertained from electrocardiograms, hospital discharge codes, and death certificates. Multivariate Cox proportional hazards regression was used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for AF associated with serum and dietary Mg quintiles. Over a median follow-up time of 20.6 years, 1,755 incident AF cases were identified. In multivariate models, lower serum Mg was associated with higher AF risk: compared to individuals in the middle quintile (=0.80-0.83 mmol/L), the HR (95% CI) of AF in quintiles 1, 2, 4, and 5 were 1.34 (1.16-1.54), 0.99 (0.85-1.16), 1.04 (0.90-1.22), and 1.06 (0.91-1.23), respectively. There was no evidence of significant interactions between serum Mg and sex or race. No association between dietary Mg and AF risk was observed. Conclusions: Lower serum Mg was associated with a higher AF risk, and this association was not different between whites and African Americans. Dietary Mg was not associated with AF risk.